Detection of a new HLA‐B*44 allele, HLA‐B*44:02:45, by monoallelic Sanger sequencing. (23rd April 2017) - Kuzmich, E.; Makarenko, O.; Alyanskiy, A.; Afanasyev, B.
Abstract : Sequence of the novel allele, HLA‐B*44:02:45, differs from HLA‐B*44:02:01:01 by 1‐nucleotide exchange in exon 2.